Endocytosis‐Inspired Zwitterionic Gel Tape for High‐Efficient and Sustainable Underoil Adhesion - Yueman Tang; Mengjie Si; Yan‐jie Wang; Jiahui Zhou; Yuming Deng; Kaishun Xia; Zhen Jiang; Dong Zhang; Si Yu Zheng; Jintao Yang (Advanced Science)
Abstract Marine oil exploration is important yet greatly increases the risk of oil leakage, which will result in severe environment pollution and economic losses. It is an urgent need to develop effective underoil adhesives. However, realizing underoil adhesion is even harder than those underwater, due to the stubborn attachment of a highly viscous oil layer on target surface. Here, inspired by endocytosis, a tough gel tape composed of zwitterionic polymer network and zwitterionic surfactants is developed. The amphiphilic surfactants can form micelle to capture the oil droplets and transport them from the interface to gel via electrostatic attraction of polymer backbone, mimicking the endocytosis and achieving robust underoil adhesion. Benefiting from the oil‐resistance of polymer backbone, the gel further realizes a combination of i) long‐term adhesion with high durability, ii) repeated adhesion in oil, and iii) renewable adhesion efficiency after exhausted use. The tape exhibits an ultra‐high adhesive toughness of 2446.86 J m−2 to stainless steel in silicone oil after 30 days' oil‐exposure; such value of adhesive toughness surpasses many of those achieved in underwater adhesion and is greater than underoil adhesion performance of commercial tape. The strategy illustrated here will motivate the design of sustainable and efficient adhesives for wet environments.